Assessing The Visiting Public's Perceptions Of The Outcomes Of Their Visit To Interactive Science And Technology Centres - Johnston, David (Curtin University, 1999)
This study investigated the problem of how to assess the visiting public's perceptions of the outcomes of their visit to an Interactive Science and Technology Centre. The study was carried out in several phases. First the researcher immersed himself as a participant observer over 15 months in the day-to-day activities of a science centre. Second, data to describe perceptions of visit outcomes were collected from one-to-one interviews with randomly selected visitors and professional staff, and four focus groups of explainers and visitors. Third, these data were used to structure the collection of further descriptions, in visitors' own words, about the visit experience. In the fourth and fifth stages, data from the second and third stages were pooled to develop two new instruments, the Perceptions of Visit Impact Instrument, a semantic differential survey designed to be administered at the point of exit from a science centre, and the Profile of Visit Outcomes Instrument, a nine part survey designed to be administered several weeks after the visit. The two instruments were refined through local review and field testing, and replication using data from large samples of randomly selected visitors at five and three centres, respectively, in Australia and New Zealand. Staff at these centres found the instruments easy to use and considered that they provided valuable data. Implications are drawn for future use of the instruments for evaluation and research.